Gastroesophageal reflux in children with chronic recurrent cough - Mardjanis Said; Rianita Syamsu; Taralan Tambunan; Badriul Hegar (Indonesian Pediatric Society, 2004)
Background Gastroesophageal reflux (GER) is reported to beone of the most common causes of chronic recurrent cough (CRC).In Indonesia, so far there is no published data concerning GER inchildren with CRC.Objectives To determine the prevalence of GER in children withCRC in general, and asthma in particular; and to describe the clini-cal profile associated with GER in these children.Methods This was a cross sectional study on children with CRCwho were investigated for GER using 24-hour esophageal pHmonitoring. GER was graded based on reflux index (RI) stated inpHmetry results i.e., mild (RI=5-10%), moderate (RI>10-20%), andsevere (RI>20%).Results Among 48 children with CRC, GER was detected in 22(46%) of them (mild GER in 14, moderate in 3, and severe in 5children). In 35 children with asthma, which is the most frequentcause of CRC in our hospital, GER was detected in 15. The preva-lence of GER increased parallel with the frequency of cough epi-sodes i.e., 10/27 in children with infrequent episodes of cough, 4/10 in children with frequent episodes of cough, and 8/11 in chil-dren with persistent cough. Clinical profiles associated with GERin these children were persistent/ frequent episodes of CRC andundernutrition.Conclusions The prevalence of GER in children with CRC was46%, and in those with asthma was 15/35. The clinical profilesassociated with GER are persistent/frequent episodes of CRCand undernutrition